The implementation of Corporate Social Responsibility (CSR) as a tool to control sustainable practices of a large retail organization in Cape Town - Mahlatshana, Kuhle (The IIE, 2020)
Sustainability alludes to meeting the needs of the present without compromising the capacity of future generations to meet their own needs. Considering this definition, humanity and societies today face challenges to sustainability and these challenges are expected to become more important in the future. Puhace (2017) also asserts that the subject of sustainability is perhaps the biggest challenge for the business industry and is viewed as a main threat to the environment and society, which needs a fast solution. However, this research paper examined the way that the large retail organization in Cape Town implements Corporate Social Responsibility as a business strategy in order to manage their sustainable practices. The qualitative research design was used as the research method while primary data was collected through two individual in-depth interviews because it enabled the researcher to pose questions to participants with the purpose of getting more perspectives, sentiments, and convictions about a specific phenomenon. Responses from the interviews indicate that the large retail organization contributes extensive CSR initiatives to a great extent in order to solve some of the sustainability issues. The findings further show that their CSR and sustainability focus are based on the following areas; educate to employ, environment efficiency, strengthen our communities, develop their local supply chain, and to drive transformation and empowerment.
Keywords: Sustainable practices; Corporate social responsibility (CSR); CSR initiatives; Business strategies; Sustainable organization